1963
DOI: 10.1071/mf9630176
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Six Species of Littoral Gastropods. I. Associations between Species and Associations with Wave Action

Abstract: The abundances and distributions of the molluscs Austrocochlea constricta, Bembicium nanum, Cellana tramoserica, Melanerita melanotragus, Montfortula conoidea, and Morula marginalba were studied on three marine, tidal, rock platforms, which varied in their degree of exposure to the action of ocean waves. The abundances and distributions of A. constricta, B. nanum, C, tramoserica, Mn. conoidea, and Mr. Marginalba were associated with wave action, but this was not the case with MI. melanotragus. The distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Bembicium nanum and Nerita atramentosa are found higher in the intertidal zone (Edgar, ). Observations of these two species on Central Coast shores followed those made by Meyer and O'Gower (), exhibiting a very low spatial overlap with C. tramoserica and M. marginalba and were consequently surveyed in separate sites in the higher zone of each shore. The number and size of each species was recorded within 35 replicate 0.5 x 0.5 m quadrats randomly positioned within each site.…”
Section: Methodsmentioning
confidence: 88%
“…Bembicium nanum and Nerita atramentosa are found higher in the intertidal zone (Edgar, ). Observations of these two species on Central Coast shores followed those made by Meyer and O'Gower (), exhibiting a very low spatial overlap with C. tramoserica and M. marginalba and were consequently surveyed in separate sites in the higher zone of each shore. The number and size of each species was recorded within 35 replicate 0.5 x 0.5 m quadrats randomly positioned within each site.…”
Section: Methodsmentioning
confidence: 88%
“…Despite some grazing gastropods being less abundant on wave‐exposed than on sheltered shores (Meyer & O'Gower 1963; Menge 1976), many intertidal grazers, including limpets, which make up the majority of grazers on seawalls (Chapman & Bulleri 2003; Bulleri et al . 2005), have been found to be more abundant on shores with intermediate to great exposure to waves (Seapy & Littler 1978; Branch 1981; Brown & Quinn 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Densities of snails were determined by collecting all snails in the quadrat and replacing them after counting. Because erosion of the spire of Morula marginalba shells occurs commonly, measurements were made of aperture-length as in Meyer and O'Gower (1963).…”
Section: Methodsmentioning
confidence: 99%
“…In the Sydney area of New South Wales, Meyer and O'Gower (1963) found that Morula marginalba was almost completely absent from shores exposed to strong waves. O'Gower and Meyer (1971) found M. marginalba to b e more abundant at the edges of pools than in the pools or on rock which dried at low tide.…”
Section: Introductionmentioning
confidence: 99%